Open Coast Seagrass Restoration. Can We Do It? Large Scale Seagrass Transplants - Paulo, Diogo; Cunha, Alexandra H.; Boavida, Joana; Serrão, Ester A.; Gonçalves, Emanuel J.; Fonseca, Mark (Frontiers in Marine Science, 2019)
Abstract Some of the major challenges in seagrass restoration on exposed open coasts are the choice of transplant design that is optimal for coastlines periodically exposed to high water motion, and understanding the survival and dynamics of the transplanted areas on a long time-scale over many years. To contribute to a better understanding of these challenges, we describe here part of a large-scale seagrass restoration program conducted in a Marine Park in Portugal. The goal of this study was to infer if it was possible to recover seagrass habitat in this region, in order to restore its ecosystem functions. To infer which methods would produce better long term persistence to recover seagrass habitat, three factors were assessed: donor seagrass species, transplant season, source location. Monitoring was done three times a year for 8 years, in which areas and densities of the planted units were measured, to assess survival and growth. The best results were obtained with the species Zostera marina transplanted during spring and summer as compared to Zostera noltii and Cymodocea nodosa. Long-term persistence of established (well rooted) transplants was mainly affected by extreme winter storms but there was evidence of fish grazing effects also. Our results indicate that persistence assessments should be done in the long term, as all transplants were successful (survived and grew initially) in the short term, but were not resistant in the long term after a winter with exceptionally strong storms. The interesting observation that only the largest (11 m2) transplanted plot of Z. marina persisted over a long time, increasing to 103 m2 in 8 years, overcoming storms and grazing, raised the hypothesis that for a successful shift to a vegetated state it might be necessary to overpass a minimum critical size or tipping point. This hypothesis was therefore tested with replicates from two donor populations and results showed effects of size and donor population, as only the larger planting units from one donor population persisted and expanded. It is recommended that in future habitat restoration efforts large planting units are considered.